ANALISIS DAYA SAING EKOWISATA DENGAN PENDEKATAN PORTER’S DIAMOND MODEL KASUS DI YOGYAKARTA - Yuniati, Nining (Kepariwisataan: Jurnal Ilmiah, 2018)
Yogyakarta is a popular destination as a place of ecotourism, currently, there are about 182 ecotourism objects. Following the development of regional and national competition, this research attempts to improve the competitiveness of ecotourism Yogyakarta by using the concept of competition strategy Porter's Diamond Model produces findings that the level of Yogyakarta's ecotourism competitiveness is at MEDIUM level or has a value of 2.39 from 3 scale. The competitiveness aspect includes the Factor Conditions (FC) at the MEDIUM level (score 2.00), Demand Conditons (FS) at the MEDIUM level (score 2.50), Firm Structure, Strategy, and Rivalry(FSSR) at the MEDIUM level (score 2.33); Support and Related Industries(SRI) at the Medium level (score 2.33); Government Role at the MEDIUM leval (score 2.50), and Chance Factor at the MEDIUM level (score 2.67). Keywords: Competitiveness, Porter’s Diamond Model, Ecotourism